Apple washers removal of insect pests and contaminants from export apples - Rogers, D.J.; Woolf, A.B.; McDonald, R.M.; Cole, L.M.; McLeod, S.; Brookfield, P.; Robertson, J.; Walker, J.T.S. (New Zealand Plant Protection, 2016)
Export markets require highquality fruit free from insects and mites of quarantine significance and with minimal or no agrichemical residues This presents a challenge for New Zealands pipfruit sector when developing novel pest management systems to meet these market requirements Brushbed apple washers are an important component of a systems approach to remove insects and mites in packhouses before fruit are exported A new apple washer using multinozzle rotors significantly reduced the incidence of insects and mites on apples Weathered residues of kaolin and hydrated lime were similarly reduced by this apple washer Assessment of fruit quality after apple washing and cool storage did not identify any commercially significant quality issues on the three apple cultivars examined Apple washer design to optimise pest removal from all locations on the fruit is discussed